0019 An In-situ Acute Paediatric Simulation Programme For General Practice Trainees. (1st November 2014) - Edelman, James; Baird, Jim; Chase, Clarissa; Lynch, Marion; Pryde, Kate; Sykes, Kim
Abstract : Background/context: Recent recommendations from the Royal College of General Practitioners and the Royal College of Paediatrics and Child Health have highlighted the need for General Practice trainees to have more focused paediatric training to develop skills and expertise in the recognition and management of acute childhood illness. 1, 2 Around 55% of GP trainees undertake a hospital-based paediatric placement, during which they will be expected to assess and provide initial care for acutely unwell children. 3, 4 Methodology: We designed a curriculum-mapped programme of 19 simulations covering common presentations of acute childhood and neonatal illness. These are delivered to GP trainees on paediatric rotations as part of a weekly departmental education programme at Salisbury Hospital. To ensure high situational fidelity, simulations are run in real-time on the paediatric ward using the whole multi-disciplinary team, and with clerical staff playing the role of parents. The trainees therefore gain realistic exposure to the assessment, diagnosis and management of the acutely unwell child in the work environment. Results/outcomes: Trainees complete a topic-specific and overall confidence questionnaire following each simulation, and an acute paediatric knowledge questionnaire at two-monthly intervals. This programme is currently being piloted and to date has run 12 sessions. Current results suggest an average increase of 1.9 (0.5–3) points in topic-specific confidence levels and attainment of higher overall confidence levels 6 weeks sooner than in a control group. Further data is still being analysed. The first full programme will be completed by August 2014. Potential impact: We hypothesise that the introduction of in-situ simulation for GP trainees in paediatric posts will improve the trainees' ability to manage acutely unwell children in hospital and will improve the recognition and emergency management of children in a community setting. We intend to extent this programme into all paediatric departments within our region to benefit trainees, staff and patients. References: Clements K. Opening the door to better healthcare: Ensuring general practice is working for children and young people. The National Children's Bureau. 2013 Royal College of Paediatrics and Child Health (RCPCH). Back to Facing the Future: An Audit of Acute Paediatric Service Standards in the UK. 2013 Isa NM, Taylor MW, Helms PJ, McLay JS. How well are general practice trainees prepared for paediatric prescribing? Br J Clin Pharmacol. 2009;67(3):370–3 Wessex General Practice Training Survey. Unpublished raw data. 2014